CHARACTERISTICS OF LAMINATED WOOD OF LOGGING WASTE OF THREE NATURAL FOREST WOOD SPECIES - Malik, Jamaludin; Santoso, Adi; Roliadi, Han (Indonesian Journal of Forestry Research, 2005)
This research is aimed to assess the characteristics of 3-ply laminated wood assembly incorporating wood waste belonged to three species i.e. bengkal (Nauclea sp.), pisang-pisang (Alponsea teysmanii Boerl), and jambu-jambu (Eugenia spp.).  The waste was procured from logged natural forests. The used adhesive was tannin-resorcinol formaldehyde.  The lamination experiment was replicated three times. The assessed characteristics were moisture content, density, formaldehyde emission, bonding strength, wood defect, and static bending strength.The resulting 3-ply laminated wood assembly (beam) has a moisture content at 4.00 - 13.90%, density 0.30 - 0.68 gram per cm3, and formaldehyde emission 0.323 - 3.199 mg per liter that tended to increase with the decrease in density of the laminated wood.  The bonding strength of the laminated wood ranges varied from 47.14 to 107.52 kg per cm2  (dry testing) and 40.76 - 79.57 kg per cm2  (wet testing).  Likewise, wood defect was about 80 - 100% (dry test) and 20 - 80% (wet test).  Static bending strength varied from 455.62 - 843.36 kg per cm2 (for MOE) and from 35,985.49 to 104,332.63 kg per cm2 (for MOR). Based on these data, the three wood waste species afforded good bending strength and they were suitable for reconstituting material for exterior-type laminated wood beam.